Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kabupaten Karawang - Nuraeni, Lia; Hermana, Cecep (Peneliti.net, 2024)
This research aims to find out, analyze and explain the influence of compensation and work motivation on the performance of Karawang Regency Public Works and Spatial Planning (PUPR) employees. By using quantitative methods and using descriptive and verification analysis, in this research the sampling technique used non-probability sampling, namely saturated sampling with a sample size of 110 respondents.The correlation between compensation (X1) and work motivation (X2) gets a correlation value of 0.663 which has a strong and unidirectional relationship level in the coefficient interval of 0.60-0.799 in the strong category. The data analysis technique used is to test hypotheses partially and simultaneously, testing is assisted using SPSS tools. The effect of partial compensation has an effect of 0.102 or 10.2% and work motivation has an effect of 0.153 or 15.3% on employee performance. The simultaneous influence of compensation and work motivation on employee performance is 0.255 or 25.5%, while the remaining 0.745 or 74.5% is influenced by other variables not studied. Both compensation and perceived work motivation have a significant effect on employee performance.